Selective hydrogenation of Dibenzo-18-crown-6 ether over highly active monodisperse Ru/γ-Al2O3 nanocatalyst - Y. R. Suryawanshi; M. Chakrabortya; S. Jauhari; S. Mukhopadhyay; K. T. Shenoy; D. Sen (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
Ru/γ-Al2O3 nanocatalyst with different metal loading was synthesized by microwave irradiated sol-vothermal technique. Synthesized nanocatalyst (4-14 nm of metal particle size)was then successfully implemented for the hydrogenation of Dibenzocrown-18-crown-6 ether (DB18C6) at 9 MPa, 393 K tem-perature and 3.5 h. It was observed that the metallic small nanoclusters produced at 4 wt% metal con-centration exhibited higher catalytic activity and resulted 96.7% conversion with 100% selectivity to-wards cis-syn-cis-dicyclohexano-18-crown-6 ether (CSC DCH18C6). © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)